Applications of EPR in radiation research - Shiotani, Masaru; Lund, Anders (Springer International Publishing, 2014)
Applications of EPR in Radiation Research is a multi-author contributed volume presented in eight themes: I. Elementary radiation processes (fundamental reaction mechanisms, low temperature radiolysis, quantum solids); II: Solid state radiation chemistry (crystalline, amorphous and heterogeneous systems); III: Biochemistry, biophysics and biology applications (radicals in biomaterials, spin trapping, free-radical-induced DNA damage); IV: Materials science (polymeric and electronic materials, materials for treatment of nuclear waste); V: Radiation metrology (EPR-dosimetry, clinical applications); VI: Geological applications; VII: Advanced techniques (pulsed and optically detected EPR, spatial distributions of radicals, radical ion pairs); VIII: Theoretical tools (density-functional calculations, spectrum simulations).